BEKERJA DI PERUSAHAAN AGRIBISNIS KOPI: MASALAH DAN SOLUSINYA - Josua Christian Simamora; Adi Nugraha (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The development of coffee agribusiness companies has triggered job opportunities for the workforce. The presence of labor is expected to meet company demand. However, over time there are company decisions that cause problems for the workforce, so that workers do their work less optimally. The purpose of this study is to identify the work problems faced by workers while working at PT. Rimbun Jaya Abadi and provide alternative solutions to overcome them. This study used a qualitative research design with a case study approach. The analysis tool used is a fishbone diagram. The research location was determined purposively. The results of this study indicate that there are work problems experienced by the personnel so that their performance is less than optimal. The lack of presence of the division head and poor communication ultimately affects the regulation of working hours, rest hours, work wages, double instructions, as well as lack of basic training for workers so that it does not work well. This causes the workforce to be less optimal in doing work and tends to be less satisfied with what has been obtained from the company. On the other hand, the company also feels the workforce's performance is not good because the demands and targets are not met. Communication needs to be improved in order to improve relations so that they can be better in the future.